Tridentate Lewis Acids: Silicon‐Functionalised 1, 3, 5‐Triethynylbenzene and 1, 3, 5‐Trivinylbenzene. Issue 22 (29th May 2018) - Schwartzen, Anna; Siebe, Lena; Schwabedissen, Jan; Neumann, Beate; Stammler, Hans‐Georg; Mitzel, Norbert W.
Abstract : Planar tridentate Lewis acids were synthesised by hydrosilylation reactions of triethynylbenzene with chlorosilanes. Hydrogenation of the rigid triethynylbenzene using hydrogen in the presence of Lindlar's catalyst resulted in the formation of trivinylbenzene. The hydrosilylation of this compound enabled the synthesis of flexible tridentate Lewis acids with SiClMe2 and SiCl2 Me, SiCl3 groups. In order to increase the acidity, the chlorine substituents of the tridentate Lewis acids were substituted by fluorine and compounds with SiF2 Me and SiF3 groups were obtained. The Lewis acidity of the isolated compounds was determined with the Gutmann–Beckett method. The results show the presence of cooperative effects of the silyl groups. Abstract : Trifunctional Lewis acids with a variety of chlorinated and fluorinates silyl groups were investigated for possible cooperative effects of the groups and found to be more pronounced for the more flexible systems.